2015
DOI: 10.4085/1062-6050-50.1.09
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Measures of Postural Control During the Star Excursion Balance Test After Acute First-Time Lateral Ankle Sprain

Abstract: Context:No researchers, to our knowledge, have investigated the immediate postinjury-movement strategies associated with acute first-time lateral ankle sprain (LAS) as quantified by center of pressure (COP) and kinematic analyses during performance of the Star Excursion Balance Test (SEBT).Objective: To analyze the kinematic and COP patterns of a group with acute first-time LAS and a noninjured control group during performance of the SEBT.Design: Case-control study. Intervention: Participants performed the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
64
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(70 citation statements)
references
References 37 publications
5
64
1
Order By: Relevance
“…Data previously published on these individuals combined measures of platform stabilometry and lower extremity joint kinematics to evaluate the sensorimotor control underpinning SEBT performance in the anterior (ANT) postero-lateral (PL) and postero-medial (PM) reach directions compared to healthy controls [6,7]. The current study pertains to data acquired from these participants one-year after sustaining their injury, thus allowing them to be classified as having chronic ankle instability or being an lateral ankle sprain coper.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data previously published on these individuals combined measures of platform stabilometry and lower extremity joint kinematics to evaluate the sensorimotor control underpinning SEBT performance in the anterior (ANT) postero-lateral (PL) and postero-medial (PM) reach directions compared to healthy controls [6,7]. The current study pertains to data acquired from these participants one-year after sustaining their injury, thus allowing them to be classified as having chronic ankle instability or being an lateral ankle sprain coper.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the tendency for a high proportion of individuals to develop chronic ankle instability following an acute lateral ankle sprain (up to 74%) [1], some recover from this injury with no symptom progression. The existence of these individuals, who have been labelled lateral ankle sprain copers [34], has given rise to a hypothesis that recovery following lateral ankle sprain injury is dependent on the sensorimotor control strategies adopted post-injury [7,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gribble et al [27] found that women demonstrated increased reach distances as compared with men in all three reach directions and attained a greater degree of hip and knee flexion at the maximal displacement following a fatigue inducing protocol. In contrast, Doherty et al [26] compared performance on the mSEBT between men and women after acute lateral ankle sprain, and found no significant difference in reach performance. However, Gribble et al [17,29] do point out kinematic reach differences in hip, knee, and ankle flexion between injured and uninjured populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies comparing the sagittal, frontal, and transverse plane kinematics during the mSEBT between sexes were primarily devoted to fatigued or injured populations only [18,[24][25][26][27][28]. Although investigators have performed kinematic analysis on healthy, non-fatigued individuals during the mSEBT, they limited their analysis to lower extremity sagittal plane angles [27].…”
Section: Introductionmentioning
confidence: 99%